Tainted Legacies and the Journal of Religious Ethics - Guth, Karen V. (Journal of religious ethics, 2023)
This essay reflects on the role academic journals like the JRE can play in facilitating and addressing tainted legacies. As an institution in religious ethics, the journal not only determines whose work is important, but it also replicates such judgments, passing certain sets of issues, concerns, and methods down from the past to the present, shaping future work. Journals highlight the systemic, structural elements of legacies that we often neglect in heated debate over how to respond to them. Consequently, they illuminate the complexity of the problems tainted legacies present. I first discuss three ways a journal like the JRE facilitates the structural features of tainted legacies in religious ethics. I then suggest how the JRE might implement a position I call the “reformer” in response to such legacies. This position emphasizes practices of moral repair designed to challenge the systemic injustices that underlay tainted legacies.